Welcome home - Labour Party leaflet, 1945 (1945)
1945 1939-1945 "Welcome home - Labour Party leaflet, 1945" [HFR0109a], 1945 In the post war period, Britain faced a housing crisis due to the loss or damage to millions of homes plus a shortage of building materials. This General Election leaflet, printed by the Labour Party in June 1945, supports local authority housing and rent controls.